Pengaruh Peran Pendamping dan Motivasi Belajar terhadap Perubahan Perilaku Keluarga Penerima Manfaat (KPM) Program Keluarga Harapan (PKH) - Febrianto, Rendi Agung; ., Utsman; RC, A. Rifai (Universitas Pendidikan Ganesha, 2020)
Poor family financial management is commonly found in Keluarga Penerima Manfaat (KPM) Program Keluarga Harapan (PKH) Kecamatan Suruh Kabupaten Semarang. Program Keluarga Harapan (PKH) with its activity called Pertemuan Peningkatan Kemampuan Keluarga (P2K2) have learning outcomes in the form of behavior change, one of them is about family financial management. In P2K2 there are internal and external factors that can affect Keluarga Penerima Manfaat (KPM) learning outcomes. This study aims to analyze the effect of companion role and learning motivation to financial management behavior change of Keluarga Penerima Manfaat (KPM) partially or simultaneously. The type of research is quantitative research. The results showed there is an effect between companion role and learning motivation to financial management behavior change of Keluarga Penerima Manfaat (KPM) Program Keluarga Harapan (PKH) Kecamatan Suruh Kabupaten Semarang.